Generation of non-relativistic electron bunches and measurement of their basic parameters - Bolotov, V.N.; Kononenko, S.I.; Muratov, V.I.; Fedorchenko, V.D. (Вопросы атомной науки и техники, 2008)
This research aims to explore a possibility of generation of short electron bunches by Bernstein-Green-Kruskal (BGK) – waves and measurement of their parameters. The experiments showed that the BGK-waves can be used to form short electron bunches with time durations ranging between 50 and 100 ps.